DISCOURSE IN ANTHROPOCENTRISM - Aliqulova Xolniso Urol qizi (TADQIQOTLAR, 2026)
Abstract.This article explores the concept of discourse within the framework of anthropocentrism  and  analyzes  the  role  of  the  human  factor  in  language  and communication. The study explains how discourse reflects human thinking, cultural values,  worldview,  and  communicative  intentions. Special  attention is given  to  the anthropocentric approach in modern linguistics, where language is studied in close relation  to  human  cognition  and  social  interaction.  The  article  also  discusses  the connection between discourse, context, and culture, emphasizing that every type of discourse carries traces of human perception and experience. Ultimately, the paper highlights  the  importance  of  discourse  analysis  in  understanding  the  relationship between language, thought, and society from an anthropocentric perspective.